Options for possible changes to the blood donation service: health economics modelling - Richard Grieve; Sarah Willis; Kaat De Corte; M Zia Sadique; Neil Hawkins; Silvia Perra; Mark Pennington; Jenny Turner; Carmel Moore; Crispin Wickenden; Catharina Koppitz; Gavin Cho; et al. (National Institute for Health Research, 2018)
Background: Evidence is required on the cost-effectiveness of alternative changes to the blood collection service. Objectives: (1) To estimate the cost-effectiveness of alternative minimum interdonation intervals between whole-blood donations. (2) To investigate donors' frequency of whole-blood donation according to alternative changes to the blood collection service. (3) To estimate the cost-effectiveness of alternative strategies for maintaining the supply of whole blood. Methods: We undertook a within-trial cost-effectiveness analysis (CEA) of the INTERVAL trial, stated preference (SP) surveys to elicit donor preferences and a CEA of different strategies for blood collection. The strategies considered were reduced minimum intervals between whole-blood donations, introduction of a donor health report and changes to appointment availability and opening times at blood collection venues. The within-trial CEA included 44,863 donors, with men randomly assigned to 12- versus 10- versus 8-week interdonation intervals, and women to 16- versus 14- versus 12-week interdonation intervals. We undertook a SP survey of non-INTERVAL donors (100,000 invitees). We asked donors to state the frequency with which they would be willing to donate blood, according to the service attribute and level. The CEA compared changes to the blood service with current practice by combining the survey estimates with information from the NHS Blood and Transpant database (PULSE) and cost data. The target population was existing whole-blood donors in England, of whom approximately 85% currently donate whole blood at mobile (temporary) blood collection venues, with the remainder donating at static (permanent) blood collection centres. We reported the effects of the alternative strategies on the number of whole-blood donations, costs and cost-effectiveness. Results: The reduced donation interval strategies had higher deferral rates caused by low haemoglobin (Hb), but increased frequency of successful donation. For men in the 8- versus 12-week arm of the INTERVAL trial [Di Angelantonio E, Thompson SG, Kaptoge S, Moore C, Walker M, Armitage J, et al. Efficiency and safety of varying the frequency of whole blood donation (INTERVAL): a randomised trial of 45 000 donors. Lancet 2017;390:2360-71], the Hb-related deferral rate was 5.7% per session versus 2.6% per session, but the average number of donations over 2 years increased by 1.71 (95% confidence interval 1.60 to 1.80). A total of 25,187 (25%) donors responded to the SP survey. For static donor centres, extending appointment availability to weekday evenings or weekends, or reduced intervals between blood donations, increased stated donation frequency by, on average, 0.5 donations per year. The CEA found that reducing the minimum interval, extending opening times to weekday evenings and extending opening times to weekends in all static donor centres would provide additional whole blood at a cost per additional unit of £10, £23 and £29, respectively, with similar results for donors with high-demand blood types. Limitations: The study did not consider the long-term rates at which donors will leave the donation register, for example following higher rates of Hb-related deferral. Conclusions: Extending opening hours for blood donation to weekday evenings or weekends for all static donor centres are cost-effective ways of increasing the supply of high-demand blood types. Future work: To monitor the effects of new strategies on long-term donation frequency. Funding: The National Institute for Health Research Health Services and Delivery Research programme.